TAFSSA stakeholder mapping: nutrition policy and awareness in Bangladesh - Nur A Mahajabin Khan; Amitaksha Nag; Parvin, Aklima; Krupnik, Timothy J. (TAFSSA, 2024)
The map provides a high-level view of the stakeholder network of the food and nutrition sub-system in Bangladesh including crop, livestock and aquaculture products. This is part of an effort to understand the networks of the agri-food system as integrated production, marketing, nutrition, and climate sub-systems. The leading question for this mapping exercise is: Who are the primary organizations, institutions and individuals in the public and private sectors that influence food (including crop, livestock and aquaculture products), nutrition policy, and nutrition awareness in Bangladesh? The following analysis uncovers the broader patterns of drivers, barriers and gaps within the nutrition sub-system network that inform potential stakeholder interventions to bring about the desired change in the agrifood system.